2020
DOI: 10.1177/2309499020907977
|View full text |Cite
|
Sign up to set email alerts
|

Suture versus screw fixation technique for tibial eminence fracture: A meta-analysis of laboratory studies

Abstract: Purpose: The aim of this study was to compare the biomechanical properties between the suture fixation technique and the screw fixation technique for tibial eminence fracture (TEF). Methods: The current study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The PubMed, Embase, and the Cochrane were searched from inception to January 2019 comparing the suture and the screw fixation technique for TEF. The results of the eligible studies were analyzed in terms of stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…5,33 Because soft tissue cut-through—or cheese-wiring—was the primary mode of suture fixation failure in our study, future studies could investigate whether suture tape constructs reduce this mode of failure and improve biomechanical outcomes. Regarding screw fixations, Ye et al 36 recently conducted a meta-analysis of studies comparing single-screw fixation versus the FiberWire suture fixation described in our study, concluding that suture fixation was superior across the spectrum of biomechanical properties. 6,9,11,20,26,29 Eggers et al 9 and Thome et al, 34 who studied skeletally mature porcine knees, concluded that the ultimate failure load of 2-screw fixation was approximately half that of FiberWire suture fixation.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…5,33 Because soft tissue cut-through—or cheese-wiring—was the primary mode of suture fixation failure in our study, future studies could investigate whether suture tape constructs reduce this mode of failure and improve biomechanical outcomes. Regarding screw fixations, Ye et al 36 recently conducted a meta-analysis of studies comparing single-screw fixation versus the FiberWire suture fixation described in our study, concluding that suture fixation was superior across the spectrum of biomechanical properties. 6,9,11,20,26,29 Eggers et al 9 and Thome et al, 34 who studied skeletally mature porcine knees, concluded that the ultimate failure load of 2-screw fixation was approximately half that of FiberWire suture fixation.…”
Section: Discussionmentioning
confidence: 59%
“…These low failure loads seen in pediatric specimens throughout this study have potential implications for postoperative rehabilitation protocols. For example, biomechanical studies in adults have found that in situ forces on the ACL-tibial spine complex can reach up kk References 2,3,6,9,15,20,[27][28][29]34,36. {{ to 303 N during early rehabilitation activities, such as contralateral toe-off during walking. 30 Because no reports of biomechanical forces on the pediatric ACL-tibial spine complex during early rehabilitation are available, we are unable to provide quantitative recommendations about the specific rehabilitation protocols that pediatric patients with TSFs should undergo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a biomechanical meta-analysis, no significant difference was found between suture and screw fixations in terms of stiffness and displacement after cyclic testing in adults. 33 In the only biomechanical study conducted for children, Johnstone et al 10 recently showed that suture and screw fixations of TEFs in pediatric human cadavers were biomechanically similar. Additionally, those authors found that pediatric bone fails at lower loads compared with adult cadaveric bone and porcine bone.…”
Section: Discussionmentioning
confidence: 99%